Investigation of the culture of safety in the medical and surgical wards of a general hospital - Petridis, E.; Lavranos, Giagkos; Raftopoulos, Vasilios (My University, 2013)
OBJECTIVE To investigate the patient safety culture and associated factors in medical and surgical wards in a tertiary general hospital in Cyprus. METHOD Data were collected from health care professionals working in the medical and surgical wards of the study hospital using the Greek version of the Safety Attitudes Questionnaire (SAQ-ICU). RESULTS From a total of 516 health care professionals eligible to participate in the survey 218 (55%) fully completed questionnaires were returned. The mean age of the participants was 34.28±10.38 years, their mean total professional experience was 11.56±10.8 years and the mean period working in the specific ward was 6.99±7.27 years. In general, the safety climate was not assessed as positive in any of the six categories which were examined, as the final scores were lower than the minimum preset positive score (≥75%). The less experienced staff marked all the scales of the questionnaire lower, with strong statistical significance for the categories teamwork (p=0.006) and working conditions (p=0.02). Those who reported that their profession poses stress on themselves and those who evaluated the quality of the services offered in their ward and the safety of the patients below the median, also reported the SAQ categories lower. Regarding the comparison between surgical and medical wards, no significant differences were identified apart from teamwork (p=0.001). CONCLUSIONS The results of this study identify a need for intervention in the categories reflected in all the scales of the SAQ questionnaire, in order for safety standards to be improved in the medical and surgical hospital wards. In particular, the role of administration needs to be upgraded, since it appears to affect the safety culture less than favourably. The less experienced staff members require more support in the reinforcement of safety standards and teamwork.
Keywords: Burnout; Empowerment; Experience; Safety; Satisfaction